Biological Sex Is Binary and Rooted in Anisogamy - Tim Janicke; Göran Arnqvist; Pierre‐André Crochet; Patrice David; Philippe Jarne; Jussi Lehtonen; Thomas Lenormand; Edward H. Morrow; Geoff A. Parker; Paul A. Saunders; Jeanne Tonnabel; Frédéric Veyrunes; et al. (Ecology Letters, 2026)
The definition of biological sex has become a renewed focus of societal debate, fuelled by the conflation of biological principles with discussions of human gender diversity. Here, we argue that conceptual clarity critically depends on separating these domains. Drawing on evolutionary theory and empirical evidence, we maintain that biological sex is best defined as a binary classification of male and female reproductive strategies rooted in anisogamy, characterised by the production of two discrete gamete types of different sizes. We stress that gamete size constitutes the ultimate criterion for biological sex and that this definition applies consistently across sexual systems, from separate‐sexed species to hermaphrodites, irrespective of variation in karyotype, hormonal profile, somatic phenotype, or behaviour. Further, we emphasise that evolutionary insights offer a coherent explanation for recurring, though not universal, associations between biological sex and patterns of sex‐specific selection, sexual dimorphism and parental care. We conclude that the definition of biological sex as a binary classification based on gamete size is a powerful scientific framework compatible with the diversity of sexual phenotypes found in anisogamous organisms and distinct from the concept of human gender.

Sexual selection in plants and animals: toward a unified framework - Jeanne Tonnabel; Patrice David; Tim Janicke (Trends in Ecology & Evolution, 2026)

Pre‐Copulatory Sexual Selection Predicts Sexual Size Dimorphism: A Meta‐Analysis of Comparative Studies - Lennart Winkler; Robert P. Freckleton; Tamás Székely; Tim Janicke (Ecology Letters, 2024)
Size differences between males and females are common across the tree of life (termed sexual size dimorphism; SSD), and have fundamental implications for ecology, life history and behaviour of both sexes. Conventionally, SSD is thought to evolve in response to sex‐specific sexual selection but more recent work suggests that ecological processes can also promote sex‐differences in size. Here, we provide a global test for the role of sexual selection in the evolution of sexual size dimorphism using data from 77 comparative studies spanning the major classes of the animal kingdom. We show that intense sexual selection typically correlates with male‐biased SSD across species. Importantly, pre‐copulatory but not post‐copulatory sexual selection predicts SSD, suggesting a pervasive role of premating male–male competition and female choice to drive sex differences in body size. Collectively, our findings suggest that pre‐copulatory sexual selection plays a major role in the evolution of male‐biased SSD.

Operational sex ratio predicts the opportunity and direction of sexual selection across animals - Tim Janicke; Edward H. Morrow (Ecology Letters, 2018)
The operational sex ratio ( OSR ) has long been assumed to be a key ecological factor determining the opportunity and direction of sexual selection. However, recent theoretical work has challenged this view, arguing that a biased OSR does not necessarily result in greater monopolisation of mates and therefore stronger sexual selection in the mate‐limited sex. Hence, the role of the OSR for shaping animal mating systems remains a conundrum in sexual selection research. Here we took a meta‐analytic approach to test whether OSR explains interspecific variation in sexual selection metrics across a broad range of animal taxa. Our results demonstrate that the OSR predicts the opportunity for sexual selection in males and the direction of sexual selection in terms of sex differences in both the opportunity for sexual selection and the Bateman gradient (i.e. the selection differential of mating success), as predicted by classic theory.

Size-assortative mating in simultaneous hermaphrodites: an experimental test and a meta-analysis - Stuart Graham; Elodie Chapuis; Stefania Meconcelli; Nicolas Bonel; Kevin Sartori; Ananda Christophe; Pilar Alda; Patrice David; Tim Janicke (Behavioral Ecology and Sociobiology, 2015)

Local adaptation of sex induction in a facultative sexual crustacean: insights from QTL mapping and natural populations of D aphnia magna - Anne C. Roulin; Jarkko Routtu; Matthew D. Hall; Tim Janicke; Isabelle Colson; Christoph R. Haag; Dieter Ebert (Molecular Ecology, 2013)
Dormancy is a common adaptation in invertebrates to survive harsh conditions. Triggered by environmental cues, populations produce resting eggs that allow them to survive temporally unsuitable conditions. D aphnia magna is a crustacean that reproduces by cyclical parthenogenesis, alternating between the production of asexual offspring and the sexual reproduction of diapausing eggs (ephippia). Prior to ephippia production, males (necessary to ensure ephippia fertilization) are produced parthenogenetically. Both the production of ephippia and the parthenogenetic production of males are induced by environmental factors. Here, we test the hypothesis that the induction of D . magna resting egg production shows a signature of local adaptation. We postulated that D aphni a from permanent ponds would produce fewer ephippia and males than D aphnia from intermittent ponds and that the frequency and season of habitat deterioration would correlate with the timing and amount of male and ephippia production. To test this, we quantified the production of males and ephippia in clonal D . magna populations in several different controlled environments. We found that the production of both ephippia and males varies strongly among populations in a way that suggests local adaptation. By performing quantitative trait locus mapping with parent clones from contrasting pond environments, we identified nonoverlapping genomic regions associated with male and ephippia production. As the traits are influenced by two different genomic regions, and both are necessary for successful resting egg production, we suggest that the genes for their induction co‐evolve.

Strategic mating effort in a simultaneous hermaphrodite - Tim Janicke; Halil Kesselring; Lukas Schärer (Behavioral Ecology and Sociobiology, 2012)

Determinants of female fecundity in a simultaneous hermaphrodite: the role of polyandry and food availability - Tim Janicke; Peter Sandner; Lukas Schärer (Evolutionary Ecology, 2011)

Sperm competition affects sex allocation but not sperm morphology in a flatworm - Tim Janicke; Lukas Schärer (Behavioral Ecology and Sociobiology, 2010)

Sex recognition in brown skuas: do acoustic signals matter? - Tim Janicke; Markus S. Ritz; Steffen Hahn; Hans-Ulrich Peter (Journal of Ornithology, 2007)

Effect of weather conditions on the communal roosting behaviour of common ravens Corvus corax with unlimited food resources - Tim Janicke; Nayden Chakarov (Journal of Ethology, 2007)

Hybridisation between South polar skua (Catharacta maccormicki) and Brown skua (C. antarctica lonnbergi) in the Antarctic Peninsula region - Markus S. Ritz; Steffen Hahn; Tim Janicke; Hans-Ulrich Peter (Polar Biology, 2006)